2010
DOI: 10.1111/j.1528-1167.2009.02517.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of seizures in comatose children in the pediatric intensive care unit: A prospective video‐EEG study

Abstract: Summary Purpose:  Studies in adult and neonatal intensive care units (ICUs) report a high prevalence of epileptic seizures in comatose patients. The prevalence of seizures in pediatric ICUs is variably reported in a few retrospective studies using different electroencephalography (EEG) methods. We aimed to determine prospectively the prevalence of epileptic seizures (clinical and subclinical) in comatose children in the pediatric ICU using continuous video‐EEG (v‐EEG) monitoring. Methods:  We performed v‐EEG i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
106
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 31 publications
13
106
1
1
Order By: Relevance
“…7 However, our data differ from a recent prospective study that reported only 7 of 100 comatose children who underwent cEEG had electrographic seizures. 12 Several issues may underlie this difference. First, the subjects enrolled had different primary medical problems.…”
Section: Results Subject and Enrollment Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 However, our data differ from a recent prospective study that reported only 7 of 100 comatose children who underwent cEEG had electrographic seizures. 12 Several issues may underlie this difference. First, the subjects enrolled had different primary medical problems.…”
Section: Results Subject and Enrollment Characteristicsmentioning
confidence: 99%
“…4 -11 One prospective study reported that only 7% of 100 comatose children had seizures detected by cEEG. 12 In this prospective observational study of critically ill children who underwent clinically indicated EEG monitoring, we aimed to 1) determine the incidence of NCS and NCSE in critically ill children using predefined institutional practice criteria for cEEG, 2) identify clinical features predictive of seizure occurrence, and 3) determine the duration of cEEG required to identify the majority of patients with seizures.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] The majority of electrographic seizures were not accompanied by any clinical signs, 1,3,8,[10][11][12][13][14] even in nonparalyzed patients. 1,14 Therefore, accurate seizure identification requires CEEG.…”
mentioning
confidence: 90%
“…[1][2][3][4][5][6][7][8][9][10][11][12] This variability is likely due to the smaller size of these cohorts, variability in case mix across institutions, and interinstitution variability in CEEG indications. Furthermore, previous studies were performed over nearly a decade, during which CEEG indications and other components of critical care have evolved.…”
mentioning
confidence: 99%
“…The majority of patients with NCS had NCS exclusively. In contrast, using strict enrollment criteria (consecutively admitted patients with a Glasgow Coma Scale of <8 and not rapidly improving, as after anesthesia) Shahwan et al [155] diagnosed NCS in only 7 of 100 pediatric patients, and 6 of these had witnessed clinical seizure activity prior to initiating the monitoring. Although patient characteristics may partially explain these discrepancies, they also suggest that without rigorous enrollment criteria it may be very difficult to circumvent the introduction of ascertainment bias into such studies [147].…”
Section: Neuromonitoring and Neuroprotection In The Picumentioning
confidence: 99%